Environmental law in a nutshell - Short Brenda (London : Sweet & Maxwell, 2003)
Explains how law can be used to protect the environment. The text introduces the legal framework used to regulate land use and pollution control together with the obligations it places on potential polluters. It incorporates issues affecting the development of environmental law.
A brief introduction to the English Legal System (for non lawyers). International and European law. Planning and environmental impact assessment. IPC and IPPC. Water pollution. Noise pollution. Atmospheric pollution. Waste management. Contaminated land. Statutory nuisance. Torts. Judicial review.
Includes index.
eng.
Keywords: Environmental law -- Great Britain